Als et al. 2011 data file - Unav (Dryad Digital Repository, 2010)
Data file with genotype data for 1010 European glass eel, 271 European eel larvae from the Sargasso Sea and 117 American eel larvae from the Sargasso Sea. Individual number: Sample code for each individual Species.ID: AA = European eel, AR American eel Transect/region: Transect in the Sargasso Sea or geographical region in Europe or North Africa Station/sample: Specific station or locality posLat: Latitudinal position posLon: Longitudinal position Date: date of sampling Length..mm: Length of eel larvae Microsatellite data are listed with one allele per column, i.e. two columns per locus. Microsatellite alleles are denoted by lenghts in bp.